2021
DOI: 10.3889/oamjms.2021.6985
|View full text |Cite
|
Sign up to set email alerts
|

Role of Monocyte-to-lymphocyte Ratio, Mean Platelet Volume-to-Platelet Count Ratio, C-Reactive Protein and Erythrocyte Sedimentation Rate as Predictor of Severity in Secondary Traumatic Brain Injury: A Literature Review

Abstract: BACKGROUND: Secondary traumatic brain injury (TBI) is injury to the brain following primary TBI because of neuroinflammation as consequences of neuronal and glial cell injury which cause release of various inflammation cytokine and chemokine. Biomarker examination to predict the severity of secondary TBI is important to provide appropriate treatment to the patient. This article reviews possibility several common laboratory parameter such as monocyte-to-lymphocyte ratio (MLR), mean platelet volume-to-platelet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 113 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…This elevation may be seen in the acute phase of TBI (first 72 h). As opposed to MLR, ESR count is not related to any acute neuroinflammatory process [11], [32].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This elevation may be seen in the acute phase of TBI (first 72 h). As opposed to MLR, ESR count is not related to any acute neuroinflammatory process [11], [32].…”
Section: Discussionmentioning
confidence: 93%
“…In this study, we found that MLR and CRP have a positive correlation in patients with TBI and are statistically significant (r = 0.215, p = 0.045). Upregulation of monocyte may be due to microglia activation after TBI and acute inflammatory response in a patient with TBI [31], [32], [33]. Escalation of monocyte leads to upregulation of proinflammatory cytokine, then activates hepatocyte to synthesize CRP [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation